2020
DOI: 10.1128/mbio.01173-20
|View full text |Cite
|
Sign up to set email alerts
|

The RNase J-Based RNA Degradosome Is Compartmentalized in the Gastric Pathogen Helicobacter pylori

Abstract: Posttranscriptional regulation is a major level of gene expression control in any cell. In bacteria, multiprotein machines called RNA degradosomes are central for RNA processing and degradation, and some were reported to be compartmentalized inside these organelleless cells. The minimal RNA degradosome of the important gastric pathogen Helicobacter pylori is composed of the essential ribonuclease RNase J and RhpA, its sole DEAD box RNA helicase, and plays a major role in the regulation of mRNA decay and adapta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…However, we found, that independently of RhpA, Hp RNase R localizes to the inner membrane of H. pylori just like the two RNA degradosome partners, RhpA and RNase J ( 11 ). Interestingly, one of the putative RNase R interactors identified by AP-MS is the membrane scaffolding protein flotillin FloA (HPB8_1315) which we previously found to promote the compartmentalization of the RNA degradosome of H. pylori ( 11 ). Altogether, these data are in favor of an ‘RNA degradation hub’ that would be compartmentalized at the membrane of H. pylori .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, we found, that independently of RhpA, Hp RNase R localizes to the inner membrane of H. pylori just like the two RNA degradosome partners, RhpA and RNase J ( 11 ). Interestingly, one of the putative RNase R interactors identified by AP-MS is the membrane scaffolding protein flotillin FloA (HPB8_1315) which we previously found to promote the compartmentalization of the RNA degradosome of H. pylori ( 11 ). Altogether, these data are in favor of an ‘RNA degradation hub’ that would be compartmentalized at the membrane of H. pylori .…”
Section: Discussionmentioning
confidence: 91%
“…We recently reported that the two partners of the RNA degradosome, RhpA and RNase J, localize to the inner membrane of H. pylori ( 11 ). Just like RhpA and RNase J, the Hp RNase R protein does not present any transmembrane segment or signal peptide ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The membrane localization of RNA degradosomes has been linked to the rate of degradation of different categories of transcripts including regulatory sRNAs (Moffitt et al, 2016), indicating a compartmentalization of RNA degradation and maturation that plays a role in transcriptome dynamics in prokaryotes. In H. pylori, we showed that the RNA degradosome, composed of the essential RNase J protein and of RhpA, the sole DEAD-box RNA helicase of this bacterium (Redko et al, 2013;El Mortaji et al, 2018), is compartmentalized at the inner membrane where it is assembled into foci whose formation is regulated and likely represent RNA degradation hubs (Tejada-Arranz et al, 2020b;Figures 1A,C). In addition, the 3 -5 exoribonuclease RNase R was also associated to the H. pylori inner membrane (Tejada-Arranz et al, 2021; Figure 1A).…”
Section: The Membrane-associated Rna Degradosome Regulates Antisense Rna Abundancementioning
confidence: 99%